Extrapulmonary sarcoidosis presenting as myositis: A rare case - Niraj Bohania; Sumeet Singla; Jagriti Nahata; Pijush Kanti Nandi; Seema Daksh; S Anuradha (Indian Journal of Rheumatology)
Sarcoidosis is a multisystem disease with dominant pulmonary involvement (90%). Isolated extrapulmonary involvement is less common. Skeletal muscle (1-2%) involvement is even rare. We report a 40 year old lady presented with easy fatigability, low grade fever for 5-6 months and generalized myalgias. Examination revealed pallor, a receding hair line, hepatomegaly and proximal muscle weakness. Investigations revealed anemia, hypercalcemia and raised serum ACE level. During hospital stay patient developed right sided hemiparesis (acute vasculitic infarct in left parietal cortex). A FDG-PET scan was done which revealed that the muscles of upper and lower limbs showed diffuse, heterogenous areas of increased FDG avidity suggestive of myositis. Final diagnosis of extrapulmonary sarcoidosis (presenting as myositis along with CNS vasculitis and hypercalcemia) was made. Patient showed marked improvement in her symptoms with immunosuppressive therapy. This case is a rare manifestation of extrapulmonary sarcoidosis and emphasizes the role of FDG-PET in diagnosing these cases.